What Factors Do Players Perceive as Methods of Retention in Battle Royale Games? - Michael John Saiger; Bobby Dewan Akram Khaleque (Press Start, 2022)
Battle Royale (BR) games are well known for their ability to not only attract but also retain a large number of players. In this paper, we attempt to identify the common themes which BR players identify as methods of retention through a qualitative thematic analysis with 11 participants. Data was gathered using semi-structured interviews and analysed through thematic analysis. Seven common themes were identified, where (1) draw of new content, (2) mechanics and action of BR games, and (3) reward systems were suggested to impact retention. Additionally, (4) social dynamics and (5) mastery were external factors outside the game that may impact retention in BR games. However, the other themes of (6) aesthetic preference and (7) unique selling points were not contributing factors in our sample. Further work is needed to understand the impact of these retention factors and how to design for these factors in game development.